Ultrathin porous nickel hydroxide nanosheet supercapacitor electrode material and preparation method and application thereof

The ultrathin porous nickel hydroxide nanosheets are prepared via dealloying and electrochemical oxidation, addressing complexity and cost issues of existing methods, resulting in a self-supporting electrode with enhanced stability and capacitance.

CN119132845APending Publication Date: 2024-12-13HUANGHUAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411384293.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Current methods for preparing nickel hydroxide electrode materials are complex, costly, and result in poor conductivity, cycle life, and agglomeration issues, necessitating a simpler and more efficient synthesis method.

Method used

A method involving the preparation of ultrathin porous nickel hydroxide nanosheets through dealloying and electrochemical oxidation of amorphous Ni-Zr-Ti alloy strips, forming a self-supporting electrode with a sandwich structure of nanoporous nickel and vertically grown nickel hydroxide nanosheets.

Benefits of technology

The method achieves improved cyclic stability, specific capacitance, and reduced internal resistance, with a capacitance retention rate of 93.6% after 6000 cycles and a maximum specific capacitance of 1120.4 F cm-3, while being cost-effective and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119132845A_ABST
    Figure CN119132845A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrathin porous nickel hydroxide nanosheet supercapacitor electrode material and a preparation method and application thereof, and belongs to the technical field of capacitor electrode materials. According to the material, an amorphous alloy serves as a core layer to play a self-supporting role, nano-porous nickel layers on the two sides provide a nickel source for in-situ growth of nickel hydroxide, and mutually-crossed ultrathin porous nickel hydroxide on the outermost layer serves as an active substance and vertically grows on the surface of the nano-porous nickel in situ; the diameter of the ultrathin porous nickel hydroxide is 0.5-2 mu m, the thickness of the ultrathin porous nickel hydroxide is 2-10 nm, and the size of holes in the nanosheet is 5-8 nm. The preparation method of the material has the advantages that the operation is simple, the cost is low, high temperature and use of nickel salt are not needed, the repeatability is good, and Ni (OH) 2 grows on nano porous nickel in situ and is a self-current-collector electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of capacitor electrode materials, and in particular relates to an ultra-thin porous supercapacitor electrode material, a preparation method, and applications thereof. Background Art

[0002] Due to the non-renewable nature of fossil fuels and the instability of renewable energy sources such as wind, solar, and geothermal energy, it is urgent to develop new energy storage devices that are cleaner, more environmentally friendly, stable, and long-lasting. Supercapacitors are widely used in transportation, aerospace, mobile communications, and other fields because of their energy density close to that of batteries, fast charging and discharging performance, safety, and environmental protection, attracting the research interest of researchers from all over the world.

[0003] Electrode materials are the main factor restricting the development of supercapacitors. Transition metal hydroxides—Ni(OH)2—have high theoretical specific capacity and high cycle stability, and are inexpensive and abundant in resources. They are expected to become a new generation of high-quality supercapacitor electrode materials. Nickel hydroxide has a variety of crystal forms and valences. During the charge and discharge process, a reversible redox reaction occurs with the conversion of different valences to produce pseudocapacitors. The specific capacity and stored energy produced are much higher than those of carbon-based electrode materials based on ion adsorption and desorption. In addition, the performance of the material is largely determined by the microscopic morphology of the material. Nanosheet-structured nickel hydroxide has a large specific surface area and a short charge transfer path. This feature is conducive to the rapid occurrence of redox reactions, thereby improving the electrochemical performance of the material. Moreover, nickel hydroxide that is firmly bonded to the matrix and evenly distributed has greatly improved electrode cycle stability and rate capability.

[0004] However, the application of Ni(OH)2 as an electrode material also has its drawbacks. Ni(OH)2 is a semiconductor material with poor conductivity, which makes its capacitance characteristics and cycle life unsatisfactory. Therefore, many researchers are committed to combining Ni(OH)2 with a conductive matrix to develop Ni(OH)2 composite materials to improve the material's rate capability and cycle stability. For example, Mingzhe Zhang's research group used a water bath method to prepare a Ni(OH)2 / CNTs composite material, and then mixed the material with acetylene black and polytetrafluoroethylene in proportion and pressed it onto nickel foam. Compared with pure Ni(OH)2, the cycle performance of this material is improved from 49.5% to 83.6% (Journal of Alloys and Compounds, 743, 2018, 1-10); Yufang Ma et al. prepared Ni(OH)2 nanosheet / 3D graphene composite materials by combining chemical vapor deposition with hydrothermal method, which showed excellent rate performance and high specific capacitance (RCS Advance, 4, 2014, 47609-47614); Zhicong Shi and Zaiping Guo's research group used the three-step method of "electrodeposition + dealloying + electrodeposition" to prepare a self-supporting Ni(OH)2@NPG / Ni foam composite electrode, which has better electrochemical performance than Ni(OH)2@Ni foam electrode (Science China Materials, 61, 2018, 353-362). Obviously, there are certain shortcomings in these Ni(OH)2 preparation methods. For example, the adhesive increases the internal resistance of the electrode and reduces the mass specific capacitance of the electrode; the hydrothermal synthesis temperature is high and the crystallinity is poor; the vapor deposition preparation technology is complex and not suitable for large-scale production; the electroactive material is grown on the conductive substrate ex situ during the electrodeposition process, and the active material is easy to agglomerate and fall off when the electrode is used; precious metals further increase the preparation cost, etc. In order to save energy and protect the environment, there is an urgent need for a low-cost, simple and effective synthesis method to prepare self-supporting Ni(OH)2 electrode materials. Summary of the invention

[0005] The technical problem to be solved by the present invention is how to address the shortcomings of current powdered Ni(OH)2 electrode materials, which require conductive agents, adhesives, and non-in-situ grown Ni(OH)2 electrode materials, with the aim of providing an ultra-thin porous nickel hydroxide nanosheet composite electrode material and a preparation method thereof.

[0006] The present invention solves the above technical problems through the following technical means:

[0007] The first aspect of the present invention provides a method for preparing an ultrathin porous nickel hydroxide nanosheet material, comprising the following steps:

[0008] (1) Preparation of Ni-Zr-Ti and Ni-Zr / Ti amorphous alloy strips:

[0009] According to the atomic percentage of each element in the target alloy, Ni, Zr, Ti or Ni, Zr / Ti are mixed, and the mixed raw materials are melted evenly to obtain Ni-Zr-Ti or Ni-Zr / Ti alloy ingots; the alloy composition is Ni x Zr y Ti z ; Wherein, x, y, and z are atomic percentages, 40≤x≤45, 0≤y≤60, 0≤z≤60, and x+y+z=100;

[0010] The obtained alloy ingot is heated to a molten state, and the alloy liquid is blown out by using an inert gas, so that the molten liquid metal solidifies on a rotating copper roller to obtain an amorphous alloy strip;

[0011] (2) Dealloying to prepare nanoporous nickel:

[0012] The amorphous alloy strip is placed in an acid solution, and then taken out and cleaned to obtain nanoporous nickel;

[0013] (3) Electrochemical oxidation synthesis of ultrathin porous nickel hydroxide nanosheets:

[0014] The nanoporous nickel is placed in an alkaline solution for electrochemical oxidation to obtain an ultrathin porous nickel hydroxide nanosheet material; the electrochemical oxidation current density is 5 to 20 mA cm -2 ; The electrochemical oxidation time is 0.5 to 5 hours.

[0015] Description: This material uses an amorphous alloy as the core layer to play a self-supporting role, and the nanoporous nickel layers on both sides provide nickel sources for the in-situ growth of nickel hydroxide. The outermost layer of intersecting ultra-thin porous nickel hydroxide serves as the active material and grows vertically in situ on the nanoporous nickel surface; the diameter of the ultra-thin porous nickel hydroxide is 0.5-2μm, the thickness is 2-10nm, and the hole size on the nanosheet is 5-8nm.

[0016] Preferably, the purity of Ni, Ti and Zr is 99.9wt.%.

[0017] Preferably, the smelting current is 60-130A.

[0018] Preferably, the amorphous alloy strip has a thickness of 20 to 50 μm and a width of 1.5 to 2 cm.

[0019] Preferably, the copper roller speed is 34-36 ms -1 .

[0020] Preferably, the inert gas is 99.99% high-purity argon.

[0021] Preferably, the acid solution is a mixed solution of H3PO4 and NH3F, in which the concentrations of NH3F and H3PO4 are both 0.02-0.5M, and the molar ratio of H3PO4 to NH3F is 1:1.

[0022] Preferably, the amorphous alloy strip is placed in the acid solution for 1 to 8 hours.

[0023] Preferably, the alkaline solution is 2M KOH or NaOH solution.

[0024] Preferably, the electrochemical oxidation current density is 10 mA cm -2 ; The electrochemical oxidation time is 2h.

[0025] The second aspect of the present invention provides an ultrathin porous nickel hydroxide nanosheet material prepared by the above preparation method.

[0026] The third aspect of the present invention proposes the use of the above-mentioned ultrathin porous nickel hydroxide nanosheet material as a supercapacitor electrode material.

[0027] The beneficial effects of the present invention are:

[0028] 1. The present invention first dealloys a nickel-based amorphous alloy in a mixed acid solution to obtain nanoporous nickel, and then electrochemically oxidizes the nanoporous nickel in a weak alkaline solution to grow nickel hydroxide nanosheets in situ. The electrode material has a sandwich structure, namely a porous Ni(OH)2 nanosheet layer on the surface, a nanoporous nickel layer in the second outer layer, and a nickel-based amorphous layer in the core. The prepared Ni(OH)2 nanosheets grow vertically in situ on the surface of the nanoporous nickel, are curved and cross each other, have a uniform structure, controllable morphology, and are firmly bonded to the substrate. The diameter of the nanosheet is 0.5-2μm, the thickness is 2-10nm, and the hole size on the nanosheet is 5-8nm. Compared with the traditional methods for preparing nickel hydroxide such as hydrothermal method, chemical precipitation method, electrodeposition method, vapor deposition method, etc., this method has the advantages of simple operation, low cost, no need for high temperature and the use of nickel salt, good repeatability, and Ni(OH)2 is grown in situ on nanoporous nickel, which is a self-current collector electrode material.

[0029] 2. Most of the common nickel hydroxides in the prior art are artificially compounded with conductive substrates (carbon nanotubes, graphene, nickel foam, etc.) by vapor deposition, hydrothermal method, electrodeposition method, etc. These methods for preparing nickel hydroxide are relatively complicated and require operations such as sealing, high temperature and high pressure. The present invention adopts electrochemical oxidation to prepare nickel hydroxide, which is undoubtedly simpler, low-cost, and basically no waste liquid is generated, greatly saving energy and labor. Second, the conductive substrate and nickel hydroxide in the nickel hydroxide composite electrode prepared by the prior art are poorly combined, and are in powder form, and conductive agents and adhesives need to be added to make electrodes, which increases the internal resistance of the composite electrode and reduces its mass specific capacitance. The electrode material of the present invention has a layered structure, and each layer is a natural composite. The electroactive material nickel hydroxide nanosheet is in situ grown on the surface of nanoporous nickel. The nanosheet is curved and cross-linked, its structure is uniform, the morphology is controllable, and it is firmly combined with the substrate, which significantly improves the cyclic stability of the material. Third, the ultra-thin porous nickel hydroxide nanosheets in the present invention have a better structural dispersion of cross-linked structures and are not easy to agglomerate. This structure is equivalent to an "ion reservoir", which increases the specific surface area of ​​the electrode material and shortens the ion diffusion distance, so that the electrode material has good performance retention and a long cycle life during use.

[0030] 3. The electrode material is composed of a tough amorphous core layer, a nanoporous nickel layer and a nickel hydroxide nanosheet layer, and each layer is a natural composite. It is a self-supporting electrode material that avoids the use of conductive agents and adhesives. The electrode preparation process is simpler and more efficient, and the cycle stability of the electrode is improved. After 6,000 constant current charge and discharge cycles, the capacitance retention rate is 93.6%.

[0031] 4. The size of ultra-thin porous nickel hydroxide nanosheets is adjustable. They grow in situ on the surface of nanoporous nickel to form an "ion reservoir", shortening the electrolyte ion transmission path and avoiding the agglomeration of electrode active substances, increasing the specific surface area of ​​the electrode material and improving the specific capacitance of the material. The maximum specific capacitance reaches 1120.4F cm -3 ;

[0032] 5. The present invention creatively combines dealloying and electrochemical oxidation technology, and the preparation process is simple and the preparation cycle is short; the prepared composite material has good mechanical integrity and can be recycled and reused, and the economic benefits are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a scanning electron microscope photograph of the ultrathin porous nickel hydroxide nanosheet prepared in Example 1.

[0034] Figure 2 This is the energy spectrum analysis diagram of the ultrathin porous nickel hydroxide nanosheets prepared in Example 1 under a scanning electron microscope.

[0035] Figure 3 This is a transmission electron microscope photograph of the ultrathin porous nickel hydroxide nanosheet prepared in Example 1.

[0036] Figure 4 This is the XRD spectrum of the ultrathin porous nickel hydroxide nanosheet composite electrode prepared in Example 1.

[0037] Figure 5 This is the constant current charge and discharge curve of the ultrathin porous nickel hydroxide nanosheet composite electrode prepared in Example 1.

[0038] Figure 6 This is the cycle stability curve of the ultrathin porous nickel hydroxide nanosheet composite electrode prepared in Example 1.

[0039] Figure 7 This is a scanning electron microscope photograph of the ultrathin porous nickel hydroxide nanosheets prepared in Example 2.

[0040] Figure 8 This is a scanning electron microscope photograph of the ultrathin porous nickel hydroxide nanosheet prepared in Example 3. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0043] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0044] Embodiment 1:

[0045] A method for preparing an ultrathin porous nickel hydroxide nanosheet material comprises the following steps:

[0046] The first step is to prepare amorphous precursor alloy strips

[0047] According to the target alloy Ni 40 Zr 20 Ti 40The atomic percentage of each element in the master alloy is 99.9wt.% of pure Ni 7.713g, pure Zr 5.994g, and pure Ti 6.292g are weighed and mixed to obtain 20g of master alloy raw material, and then the mixed metal raw materials are placed in a vacuum arc furnace, and 20g of pure Ti with a purity of 99.9wt.% is placed in the vacuum arc furnace independently without contacting with the master alloy raw material, and is melted as a deoxidizing material; under the protection of argon, the master alloy is repeatedly melted 4 times, each time for about 30 seconds to ensure the uniformity of the alloy structure; after the melting is completed, it is cooled to room temperature with the furnace to obtain Ni 40 Zr 20 Ti 40 Alloy ingot.

[0048] The alloy ingot obtained after smelting was descaled and cut into suitable sizes, placed in a quartz tube and cleaned with anhydrous ethanol. Amorphous alloy ribbons were prepared using a vacuum spinning machine. The preparation conditions were: vacuum degree 9.0×10 - 4 Pa, blowing pressure 0.1MPa, copper roller speed 36m s -1 The master alloy was placed in a quartz tube, heated to a molten state under an argon protective atmosphere, and blow-cast to form an amorphous alloy strip, preparing an alloy strip with a thickness of 20 μm and a width of 1.5 cm;

[0049] The second step is dealloying to prepare nanoporous nickel

[0050] Prepare a mixed solution of 0.05M NH4F and 0.05M H3PO4, cut off 5cm of the above nickel-based amorphous alloy strip, immerse it in the mixed solution for 2cm for dealloying treatment for 4h at room temperature, and use the remaining 3cm strip as an electrode lead. Then take out the sample and rinse it repeatedly with deionized water for 3 times to obtain nanoporous nickel;

[0051] The third step is to prepare ultrathin porous nickel hydroxide nanosheets by electrochemical oxidation

[0052] Take 100 mL of deionized water, add 20 drops of 2M KOH solution and stir evenly, then place the nanoporous nickel prepared in the second step in the weak alkaline solution and heat at 10 mA cm -2 Ultrathin porous nickel hydroxide nanosheets were synthesized by electrochemical oxidation at a current density of 2 h.

[0053] In order to detect the electrochemical performance of the prepared ultrathin porous nickel hydroxide nanosheet electrode material, the prepared composite electrode material was subjected to constant current charge and discharge test in 2M KOH solution. The test used a CHI660E electrochemical workstation with a three-electrode system. The prepared ultrathin porous nickel hydroxide nanosheet composite electrode was used as the working electrode, the platinum mesh electrode was used as the auxiliary electrode, and the Ag / AgCl electrode was used as the reference electrode. The current density of constant current charge and discharge was 0.5A cm-3 ~12A cm -3 The voltage limit is 0-0.45V. The charge and discharge current density of the cycle stability test is 4A cm -3 , the number of cycles is 6000.

[0054] The scanning electron microscope photograph of the ultrathin porous nickel hydroxide nanosheet in this embodiment is as follows: Figure 1 As shown, the ultra-thin porous nickel hydroxide nanosheets prepared in this example intersect and densely grow on the nanoporous nickel surface to form an "ion reservoir". The diameter of the nickel hydroxide nanosheet is 2μm and the thickness is 2nm. At the same time, it can be seen that the nickel hydroxide nanosheet preferentially grows in a direction perpendicular to the surface of the current collector, and the coverage rate of the nickel hydroxide nanosheets in the region on the electrode surface reaches 100% (area share).

[0055] The energy spectrum analysis diagram of the ultrathin porous nickel hydroxide nanosheet in this embodiment under a scanning electron microscope is shown in FIG. Figure 2 As shown, the main components of the sheet structure obtained in this example are nickel and oxygen, and the atomic percentage of nickel and oxygen is 1:2. Figure 4 The XRD spectrum shows that the generated flake structure is nickel hydroxide. The presence of very small amounts of Zr and Ti in the energy spectrum results indicates that the Zr and Ti elements on the surface of the strip are basically selectively dissolved during the dealloying process, and only a small amount of Zr and Ti elements exist in the amorphous substrate.

[0056] The transmission electron microscope photo of the ultrathin porous nickel hydroxide nanosheets prepared in this example is shown in FIG. Figure 3 As shown, through the transmission electron microscope photo, it can be seen that there are many small holes distributed on the nanosheet, and the diameter of the hole is 3nm. The existence of the hole is conducive to the transmission of the electrolyte and shortens the ion diffusion distance.

[0057] The XRD pattern of the ultrathin porous nickel hydroxide nanosheet composite electrode prepared in this embodiment is as follows: Figure 4 As shown, the material prepared in this example is composed of single nickel and nickel hydroxide, indicating that the Ti and Zr elements in the original alloy strip have been selectively corroded and removed by the hydrofluoric acid solution, and nickel hydroxide nanosheets have been successfully prepared on the nanoporous nickel. At the same time, the presence of the amorphous bun peak indicates that the electrode retains a certain amorphous core layer, giving the electrode structural integrity.

[0058] The constant current charge and discharge curve of the ultra-thin porous nickel hydroxide nanosheet composite electrode prepared in this embodiment is as follows: Figure 5 As shown in the figure, it can be found that there is a pair of charge-discharge platforms at different charge-discharge current densities, indicating that the electrode material has obvious pseudocapacitive characteristics. The specific capacitance of the electrode material is calculated based on the discharge time. The results show that the specific capacitance of the material increases with the decrease of current density. At 0.5A cm -3At a current density of 1.187 W, the specific capacitance reaches a maximum value of 1120.2 F cm -3 , showing excellent capacitance characteristics.

[0059] The cycle stability curve of the ultrathin porous nickel hydroxide nanosheet composite electrode prepared in this embodiment is as follows: Figure 6 As shown in the figure, it can be seen that after 1000 cycles, the specific capacitance of the material increased by 8%; after 6000 cycles, the capacitance retention rate of the material was 93.6%, showing excellent stability.

[0060] Embodiment 2:

[0061] A method for preparing an ultrathin porous nickel hydroxide nanosheet material comprises the following steps:

[0062] The first step is to prepare amorphous precursor alloy strips

[0063] According to the target alloy Ni 40 Zr 60 The atomic percentage of each element in the master alloy is 99.9wt.% of pure Ni 6.004g and pure Zr 13.996g, respectively, are weighed and mixed to obtain 20g of master alloy raw material, and then the mixed metal raw materials are placed in a vacuum arc furnace, and 20g of pure Ti with a purity of 99.9wt.% is placed in the vacuum arc furnace independently without contacting with the master alloy raw material, and is melted as a deoxidizing material; under the protection of argon, the master alloy is repeatedly melted 4 times, each time for about 30 seconds, to ensure the uniformity of the alloy structure; after the melting is completed, it is cooled to room temperature with the furnace to obtain Ni 40 Zr 60 Alloy ingot.

[0064] The alloy ingot obtained after smelting was descaled and cut into suitable sizes, placed in a quartz tube and cleaned with anhydrous ethanol. Amorphous alloy ribbons were prepared using a vacuum spinning machine. The preparation conditions were: vacuum degree 9.0×10 - 4 Pa, blowing pressure 0.1MPa, copper roller speed 35m s -1 The master alloy was placed in a quartz tube, heated to a molten state under an argon protective atmosphere, and blow-cast to form an amorphous alloy strip, preparing an alloy strip with a thickness of 20 μm and a width of 1.5 cm;

[0065] The second step is dealloying to prepare nanoporous nickel

[0066] Prepare a mixed solution of 0.02M NH4F and 0.02M H3PO4, cut off 5cm of the above nickel-based amorphous alloy strip, immerse it in the mixed solution for 2cm for dealloying treatment for 4h at room temperature, and use the remaining 3cm strip as an electrode lead. Then take out the sample and rinse it repeatedly with deionized water for 3 times to obtain nanoporous nickel;

[0067] The third step is to prepare ultrathin porous nickel hydroxide nanosheets by electrochemical oxidation

[0068] Take 100 mL of deionized water, add 20 drops of 2M KOH solution and stir evenly, then place the nanoporous nickel prepared in the second step in the weak alkaline solution and heat at 15 mA cm -2 Ultrathin porous nickel hydroxide nanosheets were synthesized by electrochemical oxidation at a current density of 2 h.

[0069] In order to detect the electrochemical performance of the prepared ultrathin porous nickel hydroxide nanosheet electrode material, the prepared composite electrode material was subjected to constant current charge and discharge test in 2M KOH solution. The test used a CHI660E electrochemical workstation with a three-electrode system. The prepared ultrathin porous nickel hydroxide nanosheet composite electrode was used as the working electrode, the platinum mesh electrode was used as the auxiliary electrode, and the Ag / AgCl electrode was used as the reference electrode. The current density of constant current charge and discharge was 0.5A cm -3 ~12A cm -3 The voltage limit is 0-0.45V. The charge and discharge current density of the cycle stability test is 4A cm -3 , the number of cycles is 6000.

[0070] The scanning electron microscope photograph of the ultrathin porous nickel hydroxide nanosheet in this embodiment is as follows: Figure 7 As shown, the ultra-thin porous nickel hydroxide nanosheets prepared in this example intersect and densely grow on the surface of nanoporous nickel to form an "ion reservoir". The diameter of the nickel hydroxide nanosheet is 0.5μm and the thickness is 4nm. At the same time, it can be seen that the nickel hydroxide nanosheet preferentially grows in a direction perpendicular to the surface of the current collector, and the coverage rate of the nickel hydroxide nanosheets in the region on the electrode surface reaches 100% (area share). From the transmission electron microscope photo, it can be seen that the hole size on the nanosheet is 5nm.

[0071] The electrochemical performance of the nickel hydroxide composite electrode material in this embodiment was tested. The results showed that: -3 At a current density of 1.38 W, the specific capacitance reaches 932.3 F cm -3 After 1000 cycles, the capacitance increased by 10%, and after 6000 cycles, the capacitance retention rate was 94.8%.

[0072] Embodiment 3:

[0073] A method for preparing an ultrathin porous nickel hydroxide nanosheet material comprises the following steps:

[0074] The first step is to prepare amorphous precursor alloy strips

[0075] According to the target alloy Ni 40 Ti60 The atomic percentage of each element in the master alloy is 99.9wt.% of each element, 8.994g of pure Ni and 11.006g of pure Ti are weighed and mixed to obtain 20g of master alloy raw material, and then the mixed metal raw materials are placed in a vacuum arc furnace, and 20g of pure Ti with a purity of 99.9wt.% is placed in the vacuum arc furnace independently without contacting with the master alloy raw material, and is melted as a deoxidizing material; under the protection of argon, the master alloy is repeatedly melted 4 times, each time for about 30 seconds to ensure the uniformity of the alloy structure; after the melting is completed, it is cooled to room temperature with the furnace to obtain Ni 40 Ti 60 Alloy ingot.

[0076] The alloy ingot obtained after smelting was descaled and cut into suitable sizes, placed in a quartz tube and cleaned with anhydrous ethanol. Amorphous alloy ribbons were prepared using a vacuum spinning machine. The preparation conditions were: vacuum degree 9.0×10 - 4 Pa, blowing pressure 0.1MPa, copper roller speed 34m s -1 The master alloy was placed in a quartz tube, heated to a molten state under an argon protective atmosphere, and blow-cast to form an amorphous alloy strip, preparing an alloy strip with a thickness of 50 μm and a width of 2 cm;

[0077] The second step is dealloying to prepare nanoporous nickel

[0078] Prepare a mixed solution of 0.1M NH4F and 0.1M H3PO4, cut off 5cm of the above nickel-based amorphous alloy strip, immerse it in the mixed solution for 2cm for dealloying treatment for 4h at room temperature, and use the remaining 3cm strip as an electrode lead. Then take out the sample and rinse it repeatedly with deionized water for 3 times to obtain nanoporous nickel;

[0079] The third step is to prepare ultrathin porous nickel hydroxide nanosheets by electrochemical oxidation

[0080] Take 100 mL of deionized water, add 50 drops of 2M KOH solution and stir evenly, then place the nanoporous nickel prepared in the second step in the weak alkaline solution and heat at 20 mA cm -2 Ultrathin porous nickel hydroxide nanosheets were synthesized by electrochemical oxidation at a current density of 4 h.

[0081] In order to detect the electrochemical performance of the prepared ultrathin porous nickel hydroxide nanosheet electrode material, the prepared composite electrode material was subjected to constant current charge and discharge test in 2M KOH solution. The test used a CHI660E electrochemical workstation with a three-electrode system. The prepared ultrathin porous nickel hydroxide nanosheet composite electrode was used as the working electrode, the platinum mesh electrode was used as the auxiliary electrode, and the Ag / AgCl electrode was used as the reference electrode. The current density of constant current charge and discharge was 0.5A cm -3 ~12A cm-3 The voltage limit is 0-0.45V. The charge and discharge current density of the cycle stability test is 4A cm -3 , the voltage limit is 0~0.45V, and the number of cycles is 6000.

[0082] The scanning electron microscope photo of the ultra-thin porous nickel hydroxide nanosheet in this embodiment shows that the ultra-thin porous nickel hydroxide nanosheets prepared in this embodiment cross each other and grow densely on the surface of nanoporous nickel to form an "ion reservoir". The diameter of the nickel hydroxide nanosheet is 0.6μm and the thickness is 9nm. At the same time, it can be seen that the nickel hydroxide nanosheet preferentially grows in a direction perpendicular to the surface of the current collector, and the coverage rate of the nickel hydroxide nanosheet in the region on the electrode surface reaches 100% (area share). From the transmission electron microscope photo, it can be seen that the hole size on the nanosheet is 8nm.

[0083] The electrochemical performance of the nickel hydroxide composite electrode material in this embodiment was tested. The results showed that: -3 At a current density of 1.3 Å, the specific capacitance reaches 944.3 F cm -3 After 1000 cycles, the capacitance increased by 9.6%, and after 6000 cycles, the capacitance retention rate was 95.2%.

[0084] Comparative Example 1:

[0085] The prepared nanoporous nickel was heated in a weak alkaline solution at 25 mA cm -2 The other conditions were the same as those in Example 1. The scanning electron microscope results showed that nickel hydroxide was seriously accumulated on the electrode surface and the morphology was uneven. The electrochemical test found that the electrode was -3 At a current density of 1.38 W, the specific capacitance is only 263.2 F cm -3 .

[0086] Comparative Example 2:

[0087] The prepared nanoporous nickel was electrochemically oxidized in deionized water, and other conditions were the same as those in Example 1. The results showed that there were only a very small number of scattered small-sized (less than 1 μm in length) nickel hydroxide nanosheet protrusions on the surface of the nanoporous nickel. The specific capacitance of the electrode material was also very low, only 300 F cm -3 .

[0088] Comparative Example 3:

[0089] The prepared amorphous alloy strip was placed in 0.6M H3PO4 and 0.6M NH3F, with other conditions being the same as in Example 2. The results showed that the electrode had very poor mechanical properties and was easily broken. From its scanning electron microscope photograph, it was observed that there were a large number of star-shaped cracks on the surface of the electrode, and the morphology of the nickel hydroxide was disorderly.

[0090] Comparative Example 4:

[0091] The target alloy is a Ni-Ti amorphous alloy with a nickel content of more than 45 at.%, and the dealloying time is extended to 2 h. Other conditions are the same as those in Example 3. It is found that the alloy strips just thrown out are relatively brittle; after dealloying, the sample is corroded and broken into small pieces, and the mechanical integrity of the initial strip cannot be maintained.

[0092] The above comparative examples 1-4 are all cases of experimental failure, indicating that arbitrarily changing the preparation parameters of the present invention will not successfully obtain porous nickel hydroxide nanosheets with uniform morphology and cross-growth, and thus it is impossible to prepare ultra-thin porous nickel hydroxide nanosheets supercapacitor electrode materials with excellent electrochemical properties.

[0093] The above examples and comparative examples show that the preparation method of the ultra-thin porous nickel hydroxide nanosheet composite electrode material in the present invention is obtained through a large amount of experiments and labor, and the optimal process conditions are obtained through continuous attempts and exploration. Only by strictly controlling the parameters of each process link can the ultra-thin porous nickel hydroxide nanosheet composite electrode material with excellent electrochemical performance be successfully obtained.

[0094] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an ultrathin porous nickel hydroxide nanosheet material, characterized in that: The following steps are involved: (1) Preparation of Ni-Zr-Ti and Ni-Zr / Ti amorphous alloy strips: According to the atomic percentage of each element in the target alloy, Ni, Zr, Ti or Ni, Zr / Ti are mixed, and the mixed raw materials are melted evenly to obtain Ni-Zr-Ti or Ni-Zr / Ti alloy ingots; the alloy composition is Ni x Zr y Ti z ; Wherein, x, y, and z are atomic percentages, 40≤x≤45, 0≤y≤60, 0≤z≤60, and x+y+z=100; The obtained alloy ingot is heated to a molten state, and the alloy liquid is blown out by using an inert gas, so that the molten liquid metal solidifies on a rotating copper roller to obtain an amorphous alloy strip; (2) Dealloying to prepare nanoporous nickel: The amorphous alloy strip is placed in an acid solution, and then taken out and cleaned to obtain nanoporous nickel; (3) Electrochemical oxidation synthesis of ultrathin porous nickel hydroxide nanosheets: The nanoporous nickel is placed in an alkaline solution for electrochemical oxidation to obtain an ultrathin porous nickel hydroxide nanosheet material; the electrochemical oxidation current density is 5 to 20 mA cm -2 ; The electrochemical oxidation time is 0.5 to 5 hours.

2. The method for preparing the ultrathin porous nickel hydroxide nanosheet material according to claim 1, characterized in that: The purity of Ni, Ti and Zr is 99.9wt.%.

3. The method for preparing the ultrathin porous nickel hydroxide nanosheet material according to claim 1, characterized in that: The smelting current is 60-130A.

4. The method for preparing the ultrathin porous nickel hydroxide nanosheet material according to claim 1, characterized in that: The amorphous alloy strip has a thickness of 20 to 50 μm and a width of 1.5 to 2 cm.

5. The method for preparing the ultrathin porous nickel hydroxide nanosheet material according to claim 1, characterized in that: The acid solution is a mixed solution of H3PO4 and NH3F. In the mixed solution, the concentrations of NH3F and H3PO4 are both 0.02-0.5M, and the molar ratio of H3PO4 to NH3F is 1:

1.

6. The method for preparing the ultrathin porous nickel hydroxide nanosheet material according to claim 1, characterized in that: The amorphous alloy strip is placed in the acid solution for 1 to 8 hours.

7. The method for preparing the ultrathin porous nickel hydroxide nanosheet material according to claim 1, characterized in that: The alkaline solution is 2M KOH or NaOH solution.

8. The method for preparing the ultrathin porous nickel hydroxide nanosheet material according to claim 1, characterized in that: The electrochemical oxidation current density is 10 mA cm -2 ; The electrochemical oxidation time is 2h.

9. An ultrathin porous nickel hydroxide nanosheet material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the ultrathin porous nickel hydroxide nanosheet material according to claim 9 as a supercapacitor electrode material.